The gut and lung microbiome across the TB disease spectrum - Perumal, Rubeshan; Somboro, Anou M.; Tulsi, Juhi; Ngcapu, Sinaye; Naidoo, Kogieleum (Frontiers in Microbiology, 2025)
Tuberculosis (TB) remains a major global health challenge, affecting approximately 10 million people annually. Susceptibility to infection by Mycobacterium tuberculosis, progression to TB, response to antimycobacterial chemotherapy, and the propensity to develop post-infectious sequelae have all been linked to a complex interplay of host and pathogen factors. Studies have revealed that communities of microorganisms colonize the human respiratory and gastrointestinal tracts and regulate regional immunity, with consequent effects on TB acquisition, progression, and resolution. An in-depth understanding of the multifaceted determinants of host susceptibility to TB, including the cross-talk between the host immune system and gut and lung microbiomes, could provide new insights into TB pathogenesis, treatment response, sequelae, and recurrence dynamics. This review explores the role of the gut-lung microbiome axis across the spectrum of TB pathogenesis, including microbial changes during and beyond TB treatment, and assesses their potential effect on treatment outcomes and the risk of TB recurrence.